2017
DOI: 10.1371/journal.pone.0178476
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive transmission of sensorimotor information in humans using an EEG/focused ultrasound brain-to-brain interface

Abstract: We present non-invasive means that detect unilateral hand motor brain activity from one individual and subsequently stimulate the somatosensory area of another individual, thus, enabling the remote hemispheric link between each brain hemisphere in humans. Healthy participants were paired as a sender and a receiver. A sender performed a motor imagery task of either right or left hand, and associated changes in the electroencephalogram (EEG) mu rhythm (8–10 Hz) originating from either hemisphere were programmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 51 publications
0
60
0
1
Order By: Relevance
“…multi-unit ultrasound arrays). While animal studies, even in large brained (and thick-skulled) animals 8 , suggest the general accuracy of linear targeting and human LIFU studies to date 10,[58][59][60] have often elected to forgo per-subject modeling of attenuation and refraction through skull, a fuller, more subject-specific, investigation of possible skull-refractory effects in naturalistic experimental settings in human subjects remains desirable going forward.…”
Section: Inhibition Of the Left Pallidum Significantly Affects All Otmentioning
confidence: 99%
“…multi-unit ultrasound arrays). While animal studies, even in large brained (and thick-skulled) animals 8 , suggest the general accuracy of linear targeting and human LIFU studies to date 10,[58][59][60] have often elected to forgo per-subject modeling of attenuation and refraction through skull, a fuller, more subject-specific, investigation of possible skull-refractory effects in naturalistic experimental settings in human subjects remains desirable going forward.…”
Section: Inhibition Of the Left Pallidum Significantly Affects All Otmentioning
confidence: 99%
“…The majority of these studies, conducted on anesthetized animals, showed a degree of variability in response to the stimulation, depending on the types and depths of anesthesia [ 24 , 28 , 31 , 37 , 40 ]. To examine the behavioral responses to FUS, without the confounding effects from anesthesia, experimentations in an awake setting are desired, and several recent studies on non-human primates and human subjects started to demonstrate the feasibility of tFUS in brain stimulation without the use of anesthesia [ 18 , 20 23 , 25 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The technique has also been applied to modulate the function of deep brain areas, for example, the hippocampus or the thalamus in rodents . Its utility has been extended to provide means for brain stimulation in the context of brain‐to‐brain interface …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Its utility has been extended to provide means for brain stimulation in the context of brain-to-brain interface. 15,16 The presence of durable changes on neural excitability induced by a brain stimulation modality, assimilating the effects such as long-term potentiation (LTP) or long-term depression (LTD), is considered one of the main features that may ultimately lead to neuroplasticity. For example, TMS applied for extended duration has shown LTD-like effects, 17 mediated by changes in activity of the N-methyl-D-aspartate (NMDA) glutamate receptor.…”
Section: Introductionmentioning
confidence: 99%